Pisikal nga pagpangabuso, importanteng mahibal-an aron mapugngan an awareness campaign on physical violence on women and children in Barangay Leon Garcia, Agdao, Davao City - Visto, Noemi Lynne B.; Comidoy, Merle Dawn S. (2018)
The research aimed to create an awareness campaign on physical violence on women and children, intended for the residents of Barangay Leon Garcia, Agdao, Davao City. The campaign will be implemented by the Proteksyon sa Kababainhan ug Kabatan-unan (PSKK), a community-based women?s organization in the said barangay which main tasks is to protect women and children against violence and abuse in the community. Using the Kohler-Evans & Barnes Model of Influence (MOI), the researcher sought that an individual undergoes four stages of learning and perceiving a new concept of idea. From developing awareness, acknowledging new perspectives, realizing benefits to self and others, and taking action and embracing influence to that new idea. Just like the model of influence, the community members in Barangay Leon Garcia will also undergo the same process upon receiving the information about physical violence when the awareness campaign will be implemented. The researcher used SWOT Analysis to determine the challenges of the PSKK in terms of its organization setting and advocacy implementation. For the awareness campaign, the researcher created communication strategies that are appropriate on the type of community member and its categorized by specific target audience such as women, children, and men. Findings showed that the failure of the PSKK to implement its advocacy and conduct activities that are initiated by the organization is rooted on the internal and external challenges that the organization is struggling with. By implementing the awareness campaign on physical violence, the researcher intends to help the PSKK to overcome and resolve its challenges. Generally, the role of the PSKK as a community-based organization is very important in forwarding the agenda of awareness on physical violence in the society in order to create a developed, peaceful, and violence-free community
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2018